2004
DOI: 10.1016/j.cardiores.2004.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol- and caveolin-rich membrane domains are essential for phospholipase A-dependent EDHF formation

Abstract: The integrity of caveolin-1-containing membrane microdomains is prerequisite for arachidonic acid recruitment and EDHF signaling in porcine arteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 32 publications
2
39
0
Order By: Relevance
“…In parallel, Cav1 KO mice also exhibit decreased Cx37, 40, and 43 expressions at the MEJ (Saliez et al, 2008). Lastly, TRPV4, Cx37, Cx40, Cx43, and SK Ca are localized in caveolae and also all colocalize and/or coimmunoprecipitate with Cav1 (Graziani et al, 2004;Absi et al, 2007;Saliez et al, 2008).…”
Section: B Potassium and Calcium Channels: A Case For The Endotheliumentioning
confidence: 78%
See 1 more Smart Citation
“…In parallel, Cav1 KO mice also exhibit decreased Cx37, 40, and 43 expressions at the MEJ (Saliez et al, 2008). Lastly, TRPV4, Cx37, Cx40, Cx43, and SK Ca are localized in caveolae and also all colocalize and/or coimmunoprecipitate with Cav1 (Graziani et al, 2004;Absi et al, 2007;Saliez et al, 2008).…”
Section: B Potassium and Calcium Channels: A Case For The Endotheliumentioning
confidence: 78%
“…It is not clear how this channel polarization occurs, but it is possible that it may be due to local plasma membrane composition because IK Ca is not located in caveolae, whereas SK Ca is located in caveolae in ECs as demonstrated by coimmunoprecipitation and experiments using sucrose gradient (Absi et al, 2007). The SK Ca portion of the EDH-mediated relaxation can be inhibited in presence of the caveolae disrupting agent MbCD, an inhibition that was reversed by addition of cholesterol (Graziani et al, 2004;Absi et al, 2007).…”
Section: B Potassium and Calcium Channels: A Case For The Endotheliumentioning
confidence: 99%
“…Conversely, very little is known about the role of caveolae in the regulation of other endothelial mediators of relaxation. Only one other study reported that caveolae may also be implicated in EDHF-mediated relaxation in pig coronary artery (Graziani et al, 2004). Furthermore, functional studies providing direct evidence that intact caveolae are essential for Life Sciences 80 (2007) 1678 -1685 www.elsevier.com/locate/lifescie NO production are limited mainly to the aorta, either from cav-1 knockout mice or pathological models, only (Darblade et al, 2001;Razani et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This study concurs with other reports that show caveolae localization or caveolin interaction for some EDHF mediators. Indeed, a study focused on EDHF pathway involving arachidonic acid metabolites (EETs) demonstrated that caveolae disruption by methylcyclodextrin cholesterol depletion, inhibits EDHF-dependent relaxation in pig coronary arteries through a decrease in EETs synthesis resulting from a defect in cPLA2 translocation [25]. More recently, a similar treatment with methylcylcodextrin on rat and porcine coronary arteries was shown to impair SKCa channel activity.…”
Section: Caveolae and Edhfmentioning
confidence: 99%